2000
DOI: 10.1002/(sici)1097-0185(20000101)258:1<90::aid-ar10>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characterization of maturation, platelet release, and senescence of human cultured megakaryocytes

Abstract: The aim of this study was to evaluate the ultrastructural features of human megakaryocytes cultured in vitro. For this purpose, pluripotent CD34(+) (cluster of differentiation 34) hematopoietic progenitor cells, obtained from the peripheral blood of healthy adult donors, were differentiated along the megakaryocytic lineage in liquid cultures by the addition of the megakaryocyte-specific growth factor thrombopoietin (TPO, 100 ng/ml). After only 6-8 days, virtually all of the CD34-derived cells expressed the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…Recent studies attempted to investigate the relationship existing between megakaryocyte maturation, apoptosis, and proplatelet formation in culture of CD34 ϩ -derived megakaryocytes. 7,8 Although unable to investigate in depth the subordination of events, this study showed that apoptosis occurred predominantly in mature megakaryocytes rather than in immature megakaryoblasts. Moreover, the kinetics of platelet release into the culture supernatants corresponded to the onset of apoptosis in these cells.…”
Section: Introductionmentioning
confidence: 76%
“…Recent studies attempted to investigate the relationship existing between megakaryocyte maturation, apoptosis, and proplatelet formation in culture of CD34 ϩ -derived megakaryocytes. 7,8 Although unable to investigate in depth the subordination of events, this study showed that apoptosis occurred predominantly in mature megakaryocytes rather than in immature megakaryoblasts. Moreover, the kinetics of platelet release into the culture supernatants corresponded to the onset of apoptosis in these cells.…”
Section: Introductionmentioning
confidence: 76%
“…However, it is thought that a specialized apoptotic process may lead to platelet assembly and release. Apoptosis has been described in megakaryocytes (56) and found to be more prominent in mature megakaryocytes as opposed to immature cells (57,58). A number of apoptotic factors, both proapoptotic and antiapoptotic, have been identified in megakaryocytes (reviewed in ref.…”
Section: Figurementioning
confidence: 99%
“…Platelets are anucleate circulating cells that are major players in the process of hemostasis and thrombosis (1,2). Platelets are produced from megakaryocytes and released into circulation, where they have a defined life span of 7-10 days in human (4 -5 days in mouse), following which they are selectively cleared by the reticuloendothelial system (3).…”
mentioning
confidence: 99%